Genome‐wide prediction of age at puberty and reproductive longevity in sows. (26th February 2013) - Tart, J. K.; Johnson, R. K.; Bundy, J. W.; Ferdinand, N. N.; McKnite, A. M.; Wood, J. R.; Miller, P. S.; Rothschild, M. F.; Spangler, M. L.; Garrick, D. J.; Kachman, S. D.; Ciobanu, D. C.
Summary Traditional selection for sow reproductive longevity is ineffective due to low heritability and late expression of the trait. Incorporation of DNA markers into selection programs is potentially a more practical approach for improving sow lifetime productivity. Using a resource population of crossbred gilts, we explored pleiotropic sources of variation that influence age at puberty and reproductive longevity. Of the traits recorded before breeding, only age at puberty significantly affected the probability that females would produce a first parity litter. The genetic variance explained by 1‐Mb windows of the sow genome, compared across traits, uncovered regions that influence both age at puberty and lifetime number of parities. Allelic variants of SNPs located on SSC5 (27–28 Mb), SSC8 (36–37 Mb) and SSC12 (1.2–2 Mb) exhibited additive effects and were associated with both early expression of puberty and a greater than average number of lifetime parities. Combined analysis of these SNPs showed that an increase in the number of favorable alleles had positive impact on reproductive longevity, increasing number of parities by up to 1.36. The region located on SSC5 harbors non‐synonymous alleles in the arginine vasopressin receptor 1A (AVPR1A) gene, a G‐protein‐coupled receptor associated with social and reproductive behaviors in voles and humans and a candidate for the observed effects. This region is characterized by high levels of linkage disequilibrium in different lines and could be exploited in marker‐assisted selection programs across populations to increase sow reproductive longevity.